2000
DOI: 10.4049/jimmunol.165.3.1573
|View full text |Cite
|
Sign up to set email alerts
|

Annexin 1 Binds to U937 Monocytic Cells and Inhibits Their Adhesion to Microvascular Endothelium: Involvement of the α4β1 Integrin

Abstract: Annexin 1 (ANX1), a calcium-binding protein, participates in the regulation of early inflammatory responses. Whereas some of its effects depend on intracellular interactions, a growing number of observations indicate that ANX1 may also act via autocrine/paracrine functions following externalization to the outer side of the plasma membrane. We studied the effects of ANX1 on leukocyte adhesion to endothelial cells using as a model system the monocytic cell line U937 and human bone marrow microvascular endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 35 publications
(36 reference statements)
6
86
0
3
Order By: Relevance
“…ANXA1 is well known as a mediator of glucocorticoid action in many body systems (33). In particular, we have previously shown glucocorticoids to limit leukocyte extravasation through the induction of ANXA1 release, whereupon ANXA1 binds to the α 4 β 1 integrin VLA 4 , blocking leukocyte adhesion to the endothelium (15). Although studies have focused on leukocyte-derived ANXA1 binding to α 4 β 1 integrin, the endothelium may also serve as a source of circulating ANXA1, constitutively limiting leukocyte adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANXA1 is well known as a mediator of glucocorticoid action in many body systems (33). In particular, we have previously shown glucocorticoids to limit leukocyte extravasation through the induction of ANXA1 release, whereupon ANXA1 binds to the α 4 β 1 integrin VLA 4 , blocking leukocyte adhesion to the endothelium (15). Although studies have focused on leukocyte-derived ANXA1 binding to α 4 β 1 integrin, the endothelium may also serve as a source of circulating ANXA1, constitutively limiting leukocyte adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported an autocrine/paracrine activity of ANXA1 in the control of pituitary adrenocorticotropin release (14) and in the blockade of monocyte migration across the inflamed peripheral endothelium (15). Consequently, we investigated whether a similar action of ANXA1 could be identified in the restoration of BBB function in vivo and in vitro.…”
Section: Anxa1 Paracellular Permeability Is Mediated By An Interactiomentioning
confidence: 99%
“…For instance direct interaction between ANXA1 and very late antigen-4 on a human monocytic cell line has recently been demonstrated. 34 In view of the lack of direct competition between peptide Ac2-26 and formyl-Met-Leu-Phe in vitro binding assays, 18 and the fact that formyl-Met-Leu-Phe and ANXA1 are clearly able to produce opposite effects in inflammation, it is likely that we have so far only scraped the surface of a complex and fascinating biological system.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylated form probably impairs cell adhesion and spreading [27], but over-expression of ITGB1BP1 stimulates cell migration [28]. Thus, the ability of ANXA1 to impair monocytes on the endothelium in vitro [21] may be mediated, at least in part, through ITGB1BP1 downregulation.…”
Section: Annexin A1 Modulates Gene Expression In Cell Linementioning
confidence: 99%
“…The peptide fMLP was purchased from Sigma (Sigma-Aldrich Corp., Poole, Dorset, UK) and 15-epi-16-(para-fluoro)-phenoxy-ATLA-methyl ester (ATLa, the methyl ester of lipoxin A4) was a generous gift from Professor C. Serhan (Harvard Medical School, Boston, USA). The doses of acetylated peptide (ANXA1 Ac2-26 ; 2 lM) were chosen on the basis of previous studies, performed both in vitro and in vivo, in which we showed that comparable biological activity were obtained when the ratio between fMLP or ATLa and ANXA1 Ac2-26 was 1:20 [13,20] furthermore such molar ratio was of 1:15 between the entire recombinant ANXA1 and the peptide Ac2-26 as described previously [21].…”
Section: Drugsmentioning
confidence: 99%